Counter-ion dependent, longitudinal unzipping of multi-walled carbon nanotubes to highly conductive and transparent graphene nanoribbons - Shinde, Dhanraj B.; Majumder, Mainak; Pillai, Vijayamohanan K. (Scientific Reports, 2014)
Here we report for the first time, a simple hydrothermal approach for the bulk production of highly conductive and transparent graphene nanoribbons (GNRs) using several counter ions from K2SO4, KNO3, KOH and H2SO4 in aqueous media, where, selective intercalation followed by exfoliation gives highly conducting GNRs with over 80% yield. In these experiments, sulfate and nitrate ions act as a co-intercalant along with potassium ions resulting into exfoliation of multi-walled carbon nanotubes (MWCNTs) in an effective manner. The striking similarity of experimental results in KOH and H2SO4 that demonstrates partially damaged MWCNTs, implies that no individual K+, SO42- ion plays a key role in unwrapping of MWCNTs, rather this process is largely effective in the presence of both cations and anions working in a cooperative manner. The GNRs can be used for preparing conductive 16 k Omega sq(-1), transparent (82%) and flexible thin films using low cost fabrication method.